Pengaruh Corporate Social Responsibility, Ukuran Perusahaan, Dan Financial Distress terhadap Auditor Switching - Hindirwan, Yoni; Kristanto, Septian Bayu (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2024)
The purpose of this research is to examine the influence of corporate social responsibility, company size and financial distress on auditor switching. This research is quantitative, and the data source obtained is secondary data. The population of this research is non-cyclical consumer companies listed on the Indonesia Stock Exchange. The research sample consisted of 30 non-cyclical consumer companies using annual financial reports and having complete data according to the variables used during 2020-2022. The method used for data analysis uses logistic regression analysis. The research results show that the Nagelkerke R Square value is 0.242, which means that corporate social responsibility, company size and financial distress can explain 24.2% of auditor switching and the rest is influenced by other variables outside this research. The test results show that: (1) corporate social responsibility has a positive and insignificant effect on auditor switching, (2) company size has a positive and significant effect on auditor switching, and (3) financial distress has a negative and insignificant effect on auditor switching.